Discoursing and Mobilizing Religious Moderation in Indonesia 2022-2024: A Critical View - Zuhri, Zuhri; Ahyunadi, Ahyunadi; Yahya, Padli Pawaid (IAIN Manado, 2025)
Abstract: Building religious behavior in society that fosters social sensitivity, sensitivity towards others, and national awareness still requires the participation of many parties, including contributions in thought, ideas, political policies, and societal momentum. As a nation with a society rich in social, religious, cultural, and political diversity, developing a narrative and discourse on religious moderation is absolutely necessary. This study critiques the ideas and movements of religious moderation in Indonesia, both in academic and political contexts, as well as what is being done by society and in the realm of digital platforms. With data and the process of diversifying patterns of discourse and movements, as well as the critical analysis conducted by the researcher, the discourse and movement of religious moderation still prioritize pragmatic interests rather than building a fundamental narrative. It is as if this movement must be accepted and practiced in daily life without realizing that such a narrative should be part of ethical religious descriptions. This means that if ethical and epistemological awareness is constructed in such a way within society, then moderate religious discourse will naturally emerge from self-awareness, without the need for it to be campaigned by the state or certain groups with significant costs. Keywords: Religion, Moderation, Episteme, Sociology, and Indonesia Abstrak: Membangun perilaku beragama di masyarakat yang menumbuhkan kepekaan sosial, kepekaan terhadap sesama, dan kesadaran berbangsa tetap memerlukan peran serta banyak pihak, termasuk sumbangan pemikiran, gagasan, kebijakan politik, dan momentum kemasyarakatan. Sebagai bangsa yang masyarakatnya kaya akan keberagaman sosial, agama, budaya, dan politik, membangun narasi dan wacana moderasi beragama mutlak diperlukan. Kajian ini mengkritisi gagasan dan gerakan moderasi beragama di Indonesia, baik dalam konteks akademis maupun politik, serta apa yang tengah dilakukan oleh masyarakat dan di ranah platform digital. Dengan data dan proses diversifikasi pola wacana dan gerakan, serta analisis kritis yang dilakukan peneliti, wacana dan gerakan moderasi beragama masih lebih mengutamakan kepentingan pragmatis ketimbang membangun narasi yang fundamental. Gerakan ini seolah-olah harus diterima dan dipraktikkan dalam kehidupan sehari-hari tanpa menyadari bahwa narasi semacam itu seharusnya menjadi bagian dari deskripsi keagamaan yang etis. Artinya, apabila kesadaran etika dan epistemologi sudah terkonstruksi sedemikian rupa dalam masyarakat, maka wacana keagamaan yang moderat akan lahir dengan sendirinya dari kesadaran itu sendiri, tanpa perlu dikampanyekan oleh negara atau kelompok tertentu dengan biaya yang tidak sedikit.Kata Kunci: Agama, Moderasi, Episteme, Sosiologi, dan Indonesia